Analisis Perkembangan Lembaga Negara Pasca Reformasi Ditinjau dari Perspektif Politik Hukum - Adityadarma Bagus Priasmoro Suryono (CV Rewang Rencang, 2020)
Legal politics is a series of concepts, principles, basic policies and statements of the will of the state authorities that contain the politics of legal formation, the politics of legal determination and the politics of application and enforcement, regarding the function of institutions and the construction of law enforcement to determine the direction, form and content of the law to be formed, the laws that apply in its territory and regarding the direction of legal development built and to achieve the objectives of the state. Indonesian legal politics underwent changes and reconstruction after the transition or change of government regime from the Old Order and New Order to the reform era. Along with the change in political configuration from authoritarian to democratic post-reform regime, many demands are voiced by elements of society to improve the conditions and structure of statehood after the new order, including in terms of state institutions.